2021
DOI: 10.3390/v13050873
|View full text |Cite
|
Sign up to set email alerts
|

The Repurposed Drugs Suramin and Quinacrine Cooperatively Inhibit SARS-CoV-2 3CLpro In Vitro

Abstract: Since the first report of a new pneumonia disease in December 2019 (Wuhan, China) the WHO reported more than 148 million confirmed cases and 3.1 million losses globally up to now. The causative agent of COVID-19 (SARS-CoV-2) has spread worldwide, resulting in a pandemic of unprecedented magnitude. To date, several clinically safe and efficient vaccines (e.g., Pfizer-BioNTech, Moderna, Johnson & Johnson, and AstraZeneca COVID-19 vaccines) as well as drugs for emergency use have been approved. However, incre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 72 publications
1
42
0
Order By: Relevance
“…A catalytic water molecule is also important and makes a strong hydrogen bond with His41 [ 5 ]. Although some allosteric binding sites have been identified for the SARS-CoV-2 M-pro [ 6 , 7 , 8 , 9 ], most of the inhibitors crystallized within the M-pro bind to the active site [ 10 ]. One strategy used to find SARS-CoV-2 M-pro inhibitors, especially at the beginning of the pandemic, was drug repositioning [ 2 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…A catalytic water molecule is also important and makes a strong hydrogen bond with His41 [ 5 ]. Although some allosteric binding sites have been identified for the SARS-CoV-2 M-pro [ 6 , 7 , 8 , 9 ], most of the inhibitors crystallized within the M-pro bind to the active site [ 10 ]. One strategy used to find SARS-CoV-2 M-pro inhibitors, especially at the beginning of the pandemic, was drug repositioning [ 2 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Quinacrine is an effective phospholipase A2 inhibitor and an antimalarial drug, harboring antiviral activity to Ebola virus, Marburg virus, dengue virus type 2, Zika virus, and SARS-CoV-2 (Balasubramanian et al, 2017;Puhl et al, 2021). Raphael et al reported that quinacrine can inhibit SARS-CoV-2 3CL pro (Eberle et al, 2021). Our study revealed that quinacrine may act at multiple stages of SARS-CoV-2 replication, including S-mediated entry and postentry.…”
Section: Discussionmentioning
confidence: 52%
“…There are several other drugs that target RdRp, such as suramin, 247 a poly-sulfonated trypan blue derivative that effectively inhibits a variety of viruses including SARS-CoV-2. 26 In the RdRp-suramin complex (Fig. 6i ), two suramin molecules occupy the catalytic cavity, which in turn blocks the RNA template-primer strand from binding to the active site and blocks NTP substrate entry into the catalytic site.…”
Section: Nonstructural Proteins Of Sras-cov-2mentioning
confidence: 99%
“…However, the emergence of multiple mutants caused by various competitive processes originating from molecule aspect (such as reading frame shifts, replication errors, etc., of virus itself), organism aspect (such as gene re-edit and recombination induced by host adaptive immune response), and population aspect (such as natural selection), 25 making it critical to identify alternative targets and develop more broad-spectrum antiviral drugs. 26 Structural biology can be used to study the pathogenic mechanism of viruses, but also provides theoretical information for drug development and optimization. For this purpose, we summarize the representative structures of SARS-CoV-2 and discuss the development of drugs, antibodies, vaccines, and other therapeutic agents for targeting these proteins or the virus.…”
Section: Introductionmentioning
confidence: 99%